2021
DOI: 10.1029/2020ea001586
|View full text |Cite
|
Sign up to set email alerts
|

Improved Determination of Europa's Long‐Wavelength Topography Using Stellar Occultations

Abstract: Europa's global shape is only poorly constrained, with our best models inferred from four Galileo limb profiles (Current values are that its axes (a, b, c) are (1562.6 km, 1560.3 km, 1559.5 km) with uncertainties of roughly 0.2 km (uncertainty estimated by comparing the different shape models in Nimmo et al. (2007)), and the topographic variance at degree 180 (the finest scale in our shape model) has an amplitude of about 20 m (Nimmo et al., 2011)) (Nimmo et al., 2007). Obtaining more precise global and region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Using the absorption cross sections for each component, these data can be analyzed to provide direct information about the composition of the atmosphere as a function of altitude above the body's surface. In addition, occultation observations can be used to provide astrometric information on the topographic shape of a target based on the time of complete signal obscuration, as is planned to be done on Europa by Europa-UVS (Abrahams et al 2021). This process has been successfully implemented for constraining the sizes of asteroids in our solar system, such as the Trojan asteroids Patroclus and Menoetius (Buie et al 2015).…”
Section: Stellar Occultationsmentioning
confidence: 99%
“…Using the absorption cross sections for each component, these data can be analyzed to provide direct information about the composition of the atmosphere as a function of altitude above the body's surface. In addition, occultation observations can be used to provide astrometric information on the topographic shape of a target based on the time of complete signal obscuration, as is planned to be done on Europa by Europa-UVS (Abrahams et al 2021). This process has been successfully implemented for constraining the sizes of asteroids in our solar system, such as the Trojan asteroids Patroclus and Menoetius (Buie et al 2015).…”
Section: Stellar Occultationsmentioning
confidence: 99%
“…However, the G/RS investigation does not plan to do so for Europa. Instead, Europa Clipper will measure the shape and size of Europa using EIS images, REASON altimetry, and Europa-UVS stellar occultations (Abrahams et al 2021).…”
Section: Radio Occultationsmentioning
confidence: 99%
“…Europa Clipper will determine Europa’s shape through a combination of REASON altimetry profiles, EIS limb profiles, and Europa-UVS occultation measurements (Abrahams et al. 2021 ). REASON altimetry profiles have an accuracy on order of 10 m (Steinbrügge et al.…”
Section: Investigationsmentioning
confidence: 99%
“…Abrahams et al. ( 2021 ) has shown that these gaps can be filled by Europa-UVS stellar occultation measurements, substantially increasing the achievable spherical harmonic degree – from 8 to 13 for very conservative assumptions about REASON performance and without limb profiles. The UVS measurements have timing accuracy of as low as 1 ms, depending on the instrument operating mode and desired precision, which for Europa-Spacecraft relative velocities of ∼1 km/s equate to measurements of chords across the body of Europa with a precision of ∼1 m (Abrahams et al.…”
Section: Investigationsmentioning
confidence: 99%
See 1 more Smart Citation